心理健康预警方法 (2023)
本发明提供了一种心理健康预警方法，包括：获取预设的第一时长内，多个学生在不同科目的课堂听课视音频数据；其中，课堂听课视音频数据包括情绪信息和肢体动作；根据每个学生的情绪信息，得到每个学生的情绪随时间变化的第一曲线；根据每个学生的肢体动作，得到每个学生的肢体动作随时间变化的第二曲线；根据每个学生的第一曲线和/或第二曲线，判断学生是否存在心理异常；当存在心理异常时，生成第一预警提示信息；将第一预警提示信息发送给终端。由此，实现了对异常心理的预警，以便于家长和老师对异常状况提前关注，从而促进学生的健康发展并提高教学效果。 The invention provides an early warning method of mental health, including the following steps: acquiring classroom video and audio data of multiple students in different subjects within a preset first duration, wherein the classroom video and audio data include emotional information and body movements; obtaining a first curve of each student's emotion changing with the time according to the emotional information of each student; obtaining a second curve of each student's body movements changing with the time according to the body movements of each student; judging whether the student has psychological abnormality according to the first curve and/or the second curve of each student; generating a first warning prompt message when the student has psycholo